Swelling Kinetics of PAAm–κ-Carrageenan Composites: A Fluorescence Technique - Evingür, Gülşen Akın; Pekcan, Önder (Informa UK Limited, 2011)
The steady-state fluorescence (SSF) technique was introduced for studying swelling of disc-shaped polyacrylamide (PAAm) gels containing various amount of κ−carrageenan (κC). They were prepared by free-radical cross-linking copolymerization. N,N′-methylenebisacrylamide (BIS) and ammonium persulfate (APS) were added as a cross-linker and an initiator, respectively. Composite gels were prepared at 80°C with pyranine as a fluorescence probe. After drying of these gels, swelling kinetics were performed in water at 60°C by real-time monitoring of the pyranine fluorescence intensity, I, which decreased as swelling proceeded. The Li–Tanaka equation was used to determine the swelling time constants, τ 1, and cooperative diffusion coefficients, D 0, from fluorescence intensity, weight, and volume variations of the gels during the swelling processes in all cases. It was observed that τ 1 decreased and D 0 increased as the κC concentrations in the composites were increased indicating that high κC gels swell faster th...
Keywords: Polyacrylamide; Composite; Hydrogels; Swelling; Kappa-carrageenan; Fluorescence